1986
DOI: 10.1172/jci112701
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of arrhythmogenic delayed and early afterdepolarizations in ferret ventricular muscle.

Abstract: Drug-induced triggered arrhythmias in heart muscle involve oscillations of membrane potential known as delayed or early afterdepolarizations (DADs or EADs). We examined the mechanism of DADs and EADs in ferret ventricular muscle. Membrane potential, tension and aequorin luminescence were measured during exposure to elevated ICa2i0, strophanthidin and/or isoproterenol (to induce DADs), or cesium chloride (to induce EADs). Ryanodine (10-'-10' M), an inhibitor of Ca2" release from the sarcoplasmic reticulum, rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
172
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(183 citation statements)
references
References 34 publications
10
172
1
Order By: Relevance
“…A DAD is a voltage depolarization caused by spontaneous calcium (Ca 2þ ) release (SCR) during the diastolic phase after a previous AP (9)(10)(11)(12)(13). If the depolarization is large enough to reach the I Na threshold, the DAD can trigger an AP causing TA.…”
Section: Introductionmentioning
confidence: 99%
“…A DAD is a voltage depolarization caused by spontaneous calcium (Ca 2þ ) release (SCR) during the diastolic phase after a previous AP (9)(10)(11)(12)(13). If the depolarization is large enough to reach the I Na threshold, the DAD can trigger an AP causing TA.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested an NCX-independent mechanism: Thus, reactivation of Ca 2+ influx via L-type Ca 2+ channels (I Ca ) during the repolarization phase may re-depolarize the membrane potential resulting in an EAD. 2,3 However, others have suggested that DADs and EADs share a common mechanism that may be NCX dependent. 4 To date, the role of chronically altered NCX expression in the generation of arrhythmia has been limited to models with increased NCX expression 5 and to animal models of heart failure or hypertrophy 1,[6][7][8][9][10] in which NCX is known to be overexpressed.…”
mentioning
confidence: 99%
“…These waves reflect spontaneous calcium release from the sarcoplasmic reticulum (Kimura et al, 1984;Marban et al, 1986). The sodium-calcium exchanger then operates in the forward mode generating a depolarizing current.…”
Section: Calcium-induced Depolarizationsmentioning
confidence: 99%